NEGARA DAN PEMBERDAYAAN PEREMPUAN (STUDI: UPAYA BPPMKB KOTA PEKANBARU DALAM MENINGKATKAN KEDUDUKAN PEREMPUAN TAHUN 2014) - Yeselin, Icha Maria; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
About the rights and freedoms of individuals, many related question to the problem of discrimination to women at the level regional and the world. To reduce the discrimination of women, need a gender equality for women to have the same position with men. One of the things that can be do by the government to seek a gender equality is through the women’s empowerment by government’s organization. This research want to see the efforts of Badan Pemberdayaan Perempuan Masyarakat dan Keluarga Berencana (BPPMKB) Kota Pekanbaru to increase the women’s position.The purpose of this research is to know how the efforts of BPPMKB Kota Pekanbaru to increase the women’s position in the stage of public in 2014. The study was made by using Qualitative Approach with qualitative descriptive methods. The location of research is BPPMKB Kota Pekanbaru. Technique of collection the data is interview and observation.The result of the research can be know that the efforts by BPPMKB Kota Pekanbaru to increase the women’s position are coaching and counseling to women, do coordination with related division, and do empowerment to women. Most of the empowerment that have been do to advance the women’s economy. The empowerment that do from coaching and counseling by BPPMKB Kota Pekanbaru still need to be expanded and improved back quality.Keywords: Empowerment, Women, Stage of Public, Gender Equality